Influence of the slight adjustment of oxides on the structural and physico-chemical properties of thin film transistor-liquid crystal display substrate glass - Jiedong Cui; Xin Cao; Lifen Shi; Zhaojin Zhong; Pingping Wang; Liyun Ma (Royal Society Open Science, 2020)
By the slight adjustment of oxides constituting thin film transistor-liquid crystal display (TFT-LCD) substrate glass, including equal mole fraction substitution of Al2O3, GeO2, B2O3, P2O5 and ZrO2 for SiO2, as well as the substitution of CaO for SrO with the total contents unchanged, the structural and physico-chemical properties of the glass was investigated by Raman spectroscopy and other measurements. The results showed that the short-range disorder brought by the substitution of GeO2, B2O3 and P2O5 for SiO2 could weaken the stability and compactness of the glass network, and the physico-chemical properties deteriorated, while the process of glass melting would become easier accordingly. The short-range disorder by the substitution of ZrO2 for SiO2 with 1% mole fraction showed a little difference with other samples. Finally, the substitution of modified cations, such as CaO and SrO, showed a smaller variation compared with the substitution of network formers. On the condition of 1% mole fraction substitution of oxides investigated, the variation of samples showed a reasonable change and the performance was basically all satisfied for the use of TFT-LCD substrate.